The Concordance of 24-Hour Urine Total Protein With Protein/Creatinine Ratios in the Diagnosis of Preeclampsia [28R]. (May 2016) - Holbert, Michael; Tuemler, Erin; Namaky, Devin
Abstract : INTRODUCTION: In 2013, the diagnostic criteria for proteinuria in the setting of suspected preeclampsia was expanded to include a urine protein/creatinine ratio of greater than 0.3 in addition to the longstanding criteria of greater than 300 milligrams of total protein in a 24 hours urine sample. The purpose of this study was to evaluate the diagnostic agreement between these two methods. METHODS: A retrospective study was performed in patients seen between July 2008 to July 2011 with elevated blood pressures that had both a 24 hour total urine protein and a contemporaneous urine protein/creatinine ratio. A analysis was performed comparing the diagnosis based upon the traditional criteria of greater than 300 milligrams of urine protein to a diagnosis based upon a urine protein/creatinine ratio greater than 0.3. RESULTS: A total of 415 charts met our inclusion criteria. Of those, 145 met the diagnosis of preeclampsia based upon urine protein/creatinine criteria and 213 met the diagnosis based upon 24 hour urine total protein criteria. Of the 415 cases, there was agreement in 299 (72%) of the cases. In addition, a 95% PPV was found using a urine protein/creatinine cutoff of 0.65 and a 95% NPV was found using a urine protein/creatinine ratio of 0.10. CONCLUSION: There is poor diagnostic concordance between the 24 hour urine total protein and the urine protein/creatinine ratio. This could be improved by using a two step approach of requiring a 24 hour urine total protein when the urine protein/creatinine ratio is between 0.10 and 0.65.